Design and analysis of double-sided flux concentrated permanent magnet linear machine with saturation relieving effect - Shen, Yiming (2023)
This paper proposes a double-sided flux concentrated permanent magnet linear machine (DS-FCPMLM) with saturation relieving effect. With the adoption of slot PMs, DS-FCPMLM can effectively relieve the primary saturation and greatly improve the thrust force density. First, the machine topology and operation principle are introduced. Then, the flux generation mechanism under dual PMs and complementary structure is analytically calculated based on magnetomotive force-permeance model, and further verified by finite element analysis. In addition, some electromagnetic performances including open-circuit characteristic, thrust force performances, demagnetization risk and power factor are comparatively studied. With the help of slot PMs, DS-FCPMLM can significantly improve the thrust force density by 63.4% compared with that only has yoke PMs, and the overload capability can be extended to nearly 4 times of the rated value. More importantly, DS-FCPMLM only consumes 1/30 PM volumes while can achieve 72.2% thrust force density compared with conventional PMLMs for a long stroke with 10 meters. Finally, a prototype of the DS-FCPMLM is carried out for experimental validation.